Do nacionalismo cultural ao anti-hitlerismo: a evolução dos escritos políticos de Thomas Mann (1914 - 1945) - Nunes, Wander Luiz Demartini (2017)
The propose of this research is to analyze the evolution of the political writings of Thomas Mann, and its relation with the context from 1914 to 1945. The papers of the period of First World War will be compared with the contemporaneous writings to the Weimar’s Republic and the works of his exile period, begun in 1933 with the rise of the Third Reich. I intend to understand how Mann, a strong defender of the German’s cause up to 1918, did not follow the flow of the extreme movements like National Socialism, but instead became an opponent of Hitler and put his intellectual service in the fight against Nazism when he emerged as one of the emirates' main names and, through the radio, made his voice come to Germany once again.